The Decline in Swedish Union Density since 2007 - Kjellberg, Anders (Nordic Journal of Working Life Studies, 2011)
Union density remains very high in Sweden. The significantly raised fees for union unemployment funds in January 2007 were followed by an unprecedented decline in the number of union members in modern Swedish history. In the course of two years union density dropped by 6 percentage points: from 77% in 2006 to 71% in 2008. As a result, the density of employers’ associations today is much higher than union density. The article below describes and analyzes union decline among different groups of workers and why it was not difficult to foresee this development when the center-right government sharply raised membership contributions to finance the state-subsidized Swedish unemployment insurance. From July 2008 the government more closely linked fund fees to the unemployment rate for each fund, thus differentiating fund fees between different groups of employees. Since the subsequent economic crisis hit private sector blue-collar workers harder than other employees, the differentiation of fees was further widened. As a consequence, total union fees (including fund fees) also varied more by time and between different categories of workers, which in turn was reflected in the development of union density. From 2006 to 2010 blue-collar density fell by 8 percentage points compared to the 4-point decline among white-collar workers. In contrast to the depression of the 1990s, union density did not increase when unemployment increased rapidly from 2008 to 2009. The article also discusses why the government failed to achieve its main goal of changing the financing system of unemployment insurance: to influence wage formation.